2012
DOI: 10.1371/journal.pone.0044615
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Molecular Mechanism of Gastric Cancer Marker Annexin A4 in Cancer Cell Proliferation Using Exon Arrays

Abstract: Gastric cancer is a malignant disease that arises from the gastric epithelium. A potential biomarker for gastric cancer is the protein annexin A4 (ANXA4), an intracellular Ca2+ sensor. ANXA4 is primarily found in epithelial cells, and is known to be involved in various biological processes, including apoptosis, cell cycling and anticoagulation. In respect to cancer, ANXA4-overexpression has been observed in cancers of various origins, including gastric tumors associated with Helicobacter pylori infection. H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 60 publications
0
32
0
1
Order By: Relevance
“…1). Anxa4 promotes vesicle aggregation in vitro, plays an important role in synaptic exocytosis and membrane repair [13,14]; it also regulates Ca 2+ -activated Cl − conductance, alters the physical properties of membranes to regulate passive membrane permeability [15][16][17], and induces calcium signaling, anticoagulation, and resistance to apoptosis [18]. Anxa4 has been reported to be associated with the progression, invasion, migration, adhesion, and drug resistance of a variety of cancers [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…1). Anxa4 promotes vesicle aggregation in vitro, plays an important role in synaptic exocytosis and membrane repair [13,14]; it also regulates Ca 2+ -activated Cl − conductance, alters the physical properties of membranes to regulate passive membrane permeability [15][16][17], and induces calcium signaling, anticoagulation, and resistance to apoptosis [18]. Anxa4 has been reported to be associated with the progression, invasion, migration, adhesion, and drug resistance of a variety of cancers [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent surgical, chemotherapeutic, immunologic, and radiation approaches have resulted in significant improvements in survival of patients with localized disease [4]; However, the successful management of patients with GC is still hampered by a lack of highly sensitive and specific biomarkers capable of predicting prognosis and the likelihood of metastasis [5]. Etiological studies have suggested that environmental factors, including diets high in salted and nitrated foods, tobacco use, alcohol consumption, and Helicobacter pylori infection are all highly associated with GC [6][7][8]. However, only some people exposed to the same environmental risk factors eventually develop GC, suggesting that genetic factors may also be involved in the etiology of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…It also takes part in calcium signaling, anticoagulation, and resistance to apoptosis [49]. Accumulated data show that annexin A4 also involves in tumor progression, invasion, metastasis, and drug resistance in various cancer types [50].…”
Section: Annexin A4 and Cancermentioning
confidence: 99%